(untitled) (Jurnal Bahasa, 2013)
This paper aims to explore the various forms and functions of discourse markers in the Malay text, written in the early of 20th century. The text, Hikayat Johor serta Pahang was written by Mejar Dato Haji Mohd. Said Sulaiman. This study applied the model of cohesion that was proposed by Halliday dan Hasan (1995). According to Halliday dan Hasan, cohesion consists of two main categories; grammatical (reference, ellipsis, substitution, conjunction), and lexical. In this model, conjunction (discourse marker) belongs to the grammatical category. This study found that discourse markers functions as event initiators and event connectors. Event initiators are marked by sebermula and al-kisah. Event connectors are expressed by three types of conjunctions: additive, causal and temporal. Temporal relations occur frequently in the text, like maka, maka apakala and apakala. Additive relations form the second most frequent, such as dan and bahawa. Finally, the least frequently used, marker are causal relations oleh itu, dalam hal itu, and dalam antara itu. This study also found that the use of discourse markers in the text is equivalent to that of other Malay classical text, which was produced in the 18th and 20th century. This study has also identified the existence of modern Malay style in the text through the use of discourse markers, such as dan and oleh itu. Keywords: discourse marker, model of cohesion, lexical, grammatical